PENEGAKAN HUKUM PIDANA DI INDONESIA TERHADAP PENGARUH NEGATIF PERKEMBANGAN CYBER CRIME - Kifli, Susiana (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2025)
The rapid development of information and communication technology is also accompanied by the widespread misuse of information and communication technology, so that it becomes a very disturbing problem, namely the occurrence of crimes committed in cyberspace or what is commonly known as